Panama : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
Panama's extensive trade and financial linkages make it vulnerable to adverse external shocks, and this would have a sizable impact on Panama's real activity. In the absence of monetary policy, macroprudential policy tools could usefully complement microprudential tools. A macroprudential supervisory body must possess the ability or power to collect and analyze firm-, market-, and global-level data to detect risks before they develop into full-blown crises. This study analyzes Panama's tax structure, performance, and administration in order to identify priority areas for further strengthening.